Apoptotic activities of brusatol in human non-small cell lung cancer cells: Involvement of ROS-mediated mitochondrial-dependent pathway and inhibition of Nrf2-mediated antioxidant response. (15th March 2021) - Xie, Jianhui; Lai, Zhengquan; Zheng, Xinghan; Liao, Huijun; Xian, Yanfang; Li, Qian; Wu, Jingjing; Ip, Siupo; Xie, Youliang; Chen, Jiannan; Su, Ziren; Lin, Zhixiu; et al.
Abstract: Brusatol occurs as a characteristic bioactive principle of Brucea javanica (L.) Merr., a traditional medicinal herb frequently employed to tackle cancer in China. This work endeavored to unravel the potential anti-cancer activity and action mechanism of brusatol against non-small cell lung cancer (NSCLC) cell lines. The findings indicated that brusatol remarkably inhibited the growth of wild-type NSCLC cell lines (A549 and H1650) and epidermal growth factor receptor-mutant cell lines (PC9 and HCC827) in a dose- and time-related fashion, and profoundly inhibited the clonogenic capability and migratory capacity of PC9 cells. Treatment with brusatol resulted in significant apoptosis in PC9 cells, as evidenced by Hoechst 33342 staining and flow cytometric analysis. The apoptotic effect was closely related to induction of G0-G1 cell cycle arrest, stimulation of reactive oxygen species (ROS) and malondialdehyde, decrease of glutathione levels and disruption of mitochondrial membrane potential. Furthermore, pretreatment with N -acetylcysteine, a typical ROS scavenger, markedly ameliorated the brusatol-induced inhibition of PC9 cells. Western blotting assay indicated that brusatol pronouncedly suppressed the expression levels of mitochondrial apoptotic pathway-associated proteins Bcl-2 and Bcl-xl, accentuated the expression of Bax and Bak, and upregulated the protein expression of XIAP, cleaved caspase-3/pro caspase-3, cleaved caspase-8/pro caspase-8, and cleaved PARP/total PARP. In addition, brusatol significantly suppressed the expression of Nrf2 and HO-1, and abrogated tBHQ-induced Nrf2 activation. Combinational administration of brusatol with four chemotherapeutic agents exhibited marked synergetic effect on PC9 cells. Together, the inhibition of PC9 cells proliferation by brusatol might be intimately associated with the modulation of ROS-mediated mitochondrial-dependent pathway and inhibition of Nrf2-mediated antioxidant response. This novel insight might provide further evidence to buttress the antineoplastic efficacy of B. javanica, and support a role for brusatol as a promising anti-cancer candidate or adjuvant to current chemotherapeutic medication in the therapy of EGFR-mutant NSCLC.